2021
DOI: 10.1055/s-0041-1732798
|View full text |Cite
|
Sign up to set email alerts
|

Internal Pudendal Artery Angioplasty to Rescue Penile Gangrene.

Abstract: Internal pudendal artery (IPA) is a branch of internal iliac artery that mainly supplies the perineal organs and external genitalia. Any obstruction in the artery seen in diabetics, hypertensives, or chronic kidney disease-induced calciphylaxis leads to decreased blood flow and may cause gangrene. IPA angioplasty is a known therapeutic procedure for erectile dysfunction and has shown promising results. However, similar procedure to relieve arterial blockade may be used to stop spread of penile gangrene and sav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Shah and colleagues reported a known case of hypertension, diabetes, and chronic renal failure who underwent circumcision for phimosis and developed gangrene of the glans penis two weeks later. The patient underwent internal pudendal artery angioplasty and a partial penectomy [ 10 ]. Kim et al reported unexpected penile glans ischemic necrosis after internal pudendal arterial embolization in a patient with a post-traumatic internal pudendal artery-urethral fistula [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shah and colleagues reported a known case of hypertension, diabetes, and chronic renal failure who underwent circumcision for phimosis and developed gangrene of the glans penis two weeks later. The patient underwent internal pudendal artery angioplasty and a partial penectomy [ 10 ]. Kim et al reported unexpected penile glans ischemic necrosis after internal pudendal arterial embolization in a patient with a post-traumatic internal pudendal artery-urethral fistula [ 11 ].…”
Section: Discussionmentioning
confidence: 99%